Multi-electron transfer to and from organic molecules - Batchelor-McAuley, C; C Batchelor-McAuley (2012)
Herein, the influence of protonation and adsorption upon the redox and electrocatalysis of quinone species - specifically anthraquinone derivatives – is investigated. Through the comparison of the measured rate constants of one-electron reductions of a family of quinones in acetonitrile at both graphite and gold electrodes, it was confirmed that the redox potential indirectly influences the rate of electron transfer in a manner consistent with the potential-dependence of the density of states. In aqueous media, the voltammetric response of both anthraquione-2-sulfonate (AQMS) and anthraquinone-2,6-disulfonate (AQDS) was measured over the full aqueous pH range. A model is provided which is able to describe not just the variation in the formal potential but also the peak height as a function of pH. Importantly, this model predicts that the formal potential for the first (Ef1) and second (Ef2) electron transfers are comparable in magnitude (E^θ _f2−E^_θf1 equals -15mV for AQMS and -36mV for AQDS). This quantitative model is then further extended to consider the situation in which the system is not fully buffered, giving insight into the change of pH at the electrode surface during experimentation. Adsorption to graphitic electrodes can impart a strong influence on the measured voltammetric response. It is demonstrated that through the pre-exposure of a newly prepared graphitic electrode to organic solvents, these adsorption processes can be predominantly blocked. Moreover, it is shown that the electroactivity of the electrode is not significantly altered. This thesis also highlights two cases in which adsorption of the electroactive species may be used to positive effect. First, the surface adsorption of anthraquinone-2-monosulfonate is studied on a graphite electrode, where it is demonstrated that the heterogeneity of the electrode surface may be probed through studying the electrochemical response of the adsorbed species. From this work it is concluded that the rate of electron transfer at the graphitic basal plane is 2-3 orders of magnitude lower than that observed on the edge plane sites. Second, the co-adsorption of DNA and anthraquinone-2-monosulfonate is used as an indirect method to measure the solution phase concentration of DNA (LOD = 8.8μM). The reduced form of anthraquinone is also known to readily reduce oxygen. Through the use of a boron-doped diamond electrode it was possible to directly study the anthraquinone mediated reduction mechanism. Significantly, the voltammetric response indicates the reduction of the oxygen via the semi-quinone intermediate (kf = 4.8 × 10⁹ mol⁻¹ dm³ s⁻¹) is over two orders of magnitude faster than the reaction involving the di-reduced form (kf = 1 × 10⁷ mol⁻¹ dm³ s⁻¹). More importantly, this work provides voltammetric evidence for the existence of the semi-quinone species. This work is subsequently extended through the investigation of the poorly soluble anthraquinone derivative quinizarin. Not only is it possible to detect voltammetrically this biologically relevant species to concentrations as low as 5nM (100ppt), but the methodology also allows the electrochemistry of the quinizarin species to be probed, something which was not previously possible.